2009
DOI: 10.1897/08-622.1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment of 17α‐ethinylestradiol in surface waters of the United States and Europe

Abstract: An evaluation of measured and predicted concentrations of 17-ethinylestradiol in surface waters of the United States and Europe was conducted to develop expected long-term exposure concentrations for this compound. Measured environmental concentrations (MECs) in surface waters were identified from the literature. Predicted environmental concentrations (PECs) were generated for European and U.S. watersheds using the GREAT-ER and PhATE models, respectively. The majority of MECs are nondetect and generally consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 26 publications
1
60
0
2
Order By: Relevance
“…Female fecundity can also be reduced through estrogen exposure, which can potentially reduce population growth rates [22]. Although the exposure concentrations in these studies were high compared to those typically experienced by wild fish populations [23], exposures to EE 2 at concentrations below 1 ng/L during the period of sexual development, have been shown to result in feminized gonads in roach [19] and decreased egg fertilization and female-skewed sex ratios in fathead minnows [24]. Evidence from wild roach living in UK rivers has similarly shown that feminized fish (generally less than 10% of males) with large numbers of eggs in their gonads have impaired semen quality [25] and severely (up to 76%) reduced reproductive success [26].…”
Section: Introductionmentioning
confidence: 99%
“…Female fecundity can also be reduced through estrogen exposure, which can potentially reduce population growth rates [22]. Although the exposure concentrations in these studies were high compared to those typically experienced by wild fish populations [23], exposures to EE 2 at concentrations below 1 ng/L during the period of sexual development, have been shown to result in feminized gonads in roach [19] and decreased egg fertilization and female-skewed sex ratios in fathead minnows [24]. Evidence from wild roach living in UK rivers has similarly shown that feminized fish (generally less than 10% of males) with large numbers of eggs in their gonads have impaired semen quality [25] and severely (up to 76%) reduced reproductive success [26].…”
Section: Introductionmentioning
confidence: 99%
“…EE 2 is the main component of most contraceptive pills, and is released into the environment through waste water at concentrations ranging from below detectable levels up to 200-300 ng/L (Hannah et al, 2009;Kolpin et al, 2002;Laurenson et al, 2014;Ternes et al, 1999). The doses currently released into the environment have been shown to be harmful to aquatic animals (Aris et al, 2014), with a predicted noeffect-concentration for aquatic organisms at 0.1 ng/L (Caldwell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These catalysts were compared to more conventional catalysts including TiO 2 . The synthetic estrogens: 171␣-ethinyl estradiol and estriol were selected as model compounds for study because they are of concern to federal and state environmental protection agencies and EPA [8][9][10][11][12][13][14]. The degradation rates and mechanisms were compared based on catalyst type.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC-MS/MS is a favored choice for mechanism development because there is no need for solvent extraction that remove or complex with degradation products. The particular HPLC-MS/MS method has been successfully used by the Patterson group and others for pharmaceuticals and other organics in water [4,8,[36][37][38][39][40]. The mechanisms for the degradation of each pharmaceutical were compared based on catalyst type and duration of UV exposure.…”
Section: Introductionmentioning
confidence: 99%